2000
DOI: 10.1002/jor.1100180510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biomechanical and biochemical properties of cartilage from human knee and ankle pairs

Abstract: Cartilage was obtained from eight matched knee (tibiofemoral and femoropatellar) and ankle (talocrural) joints of five different donors (both left and right from donors 14, 22, and 38 years of age, and left only from donors 31 and 45 years of age) within 24 hours of death. All cartilage was graded as normal by the macroscopic visual Collins' scale and the histological Mankin scale. Cylindrical disks of cartilage were harvested from 10 sites within the tibiofemoral and femoropatellar joint surfaces and four sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
215
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(251 citation statements)
references
References 38 publications
33
215
1
2
Order By: Relevance
“…The aggregate modulus in our study was within the range previously reported for normal human lateral femoral condyles [4,22,50]. However, the calculated dynamic modulus was lower than described by Kurkijärvi et al [22].…”
Section: Discussionsupporting
confidence: 87%
“…The aggregate modulus in our study was within the range previously reported for normal human lateral femoral condyles [4,22,50]. However, the calculated dynamic modulus was lower than described by Kurkijärvi et al [22].…”
Section: Discussionsupporting
confidence: 87%
“…36 In addition, there is no consensus in the literature regarding the proteoglycan and collagen synthesis characteristics between ankle and knee chondrocytes. 12,14,15,36 On the basis of the findings of this study, chondrocytes from the tibial plafond produced higher amounts of collagen and GAG and also had a superior capacity for generating new tissue, as compared with those isolated from the femur. In contrast, chondrocytes isolated from the talar dome appeared to have worse biomechanical properties and a worse biological profile than femur chondrocytes.…”
Section: Disparity In Articulating Surfaces Of Anklementioning
confidence: 68%
“…A few reports describe the anatomic and biomechanical differences among the cartilage comprising different joints, which could be responsible for the disparity in the prevalence of osteoarthritis. 11,12 Significant topographic variations in the cartilage material properties have been described that may be related to the increased risk of degeneration. 13 In addition, variations in the biochemical properties of the extracellular matrix and the metabolic activity of the chondrocytes between the ankle and the knee joint have been reported.…”
mentioning
confidence: 99%
“…Consequently, the ankle experiences more force per square centimeter than the knee or hip [37]. Functionally, the ankle acts mainly as a rolling joint with high congruency [41]. The knee, however, deals with higher shear forces by acting more as a rolling, sliding, and rotating joint during motion [41].…”
Section: Discussionmentioning
confidence: 99%